Outcomes in primary cutaneous diffuse large B‐cell lymphoma, leg type. Issue 5 (28th August 2021) - Kraft, Robert M.; Ansell, Stephen M.; Villasboas, Jose C.; Bennani, N. Nora; Wang, Yucai; Habermann, Thomas M.; Thanarajasingam, Gita; Lester, Scott C.; Macon, William; Inwards, David J.; Porrata, Luis F.; Micallef, Ivana N.; et al.
Abstract: Primary cutaneous diffuse large B‐cell lymphoma, leg type (PCDLBCL, LT) is a rare, aggressive lymphoma characterized by skin involvement predominantly in the lower extremities. Immunochemotherapy with or without involved‐site radiation therapy (ISRT) is considered standard front‐line therapy. Over‐expression of PD‐L1/PD‐L2 is seen in a high proportion of PCDLBCL, LT cases, but efficacy of immune checkpoint inhibitors (ICI) in relapsed/refractory, PCDLBCL, LT has not been thoroughly studied. We conducted a retrospective cohort study of patients diagnosed with PCDLBCL, LT seen at Mayo Clinic from 1 January 2000 to 31 December 2020. Using the Kaplan–Meier method, we calculated progression‐free survival, duration of response, and overall survival in patients who received front‐line rituximab, cyclophosphamide, doxorubicin, vincristine, and prednisone (R‐CHOP) with and without ISRT, and salvage ICI therapy for relapsed/refractory disease. A total of 28 patients with PCDLBCL, LT were identified. The median PFS in patients treated with R‐CHOP plus ISRT was 58 months (95% CI: 18–112) compared to 14 months (95% CI: 5–not reached; p = 0.04) in those treated with R‐CHOP without ISRT. The median PFS from salvage ICI therapy was 10 months (95% CI: 4–not reached), and median DOR from salvage ICI therapy was 23 months [95% CI: 4–26]. R‐CHOP with ISRT had a significantly longer median PFS compared to R‐CHOP without ISRT as front‐line therapy for PCDLBCL, LT. ICIs may have a role in treating relapsed/refractory disease as reasonable activity in heavily pre‐treated patients was observed in this study.